Debates, rhetoric and political action : practices of textual interpretation and analysis - Wiesner, Claudia; Haapala, Taru ; Palonen, Kari (Palgrave Macmillan, 2020)
This book explicates how debates and documents can be understood, interpreted and analysed as political action. It offers the reader both a theoretical introduction and practical guidance. The authors deploy the perspective that debates are to be understood as political activity, and documents can be regarded as frozen debates. The first chapter discusses what is to be understood as politics and political. The second chapter explains the concept of debate as an exchange of arguments in speaking pro and contra. The third chapter presents concrete approaches, research practices and experiences that help analysing debates and documents as politics. The fourth chapter consists of a number of case studies that demonstrate how researchers can proceed in analysing parliamentary debates, documents, laws, and media articles. This book will be of use to all students and scholars interested in analysing texts and documents, as well as in political rhetoric and parliamentary debates.Contents: Preface -- 1. Understanding Debate as Politics -- 2. Reading debates politically -- 3. Research practices and operations in studying debates and documents -- 4. Examples of analysing debates as politics -- Concluding notes -- References -- Index.